Obtaining of strontium doped fluorapatite powders - Sayenko, S.Yu. (Functional Materials, 2015)
Possibility of obtaining powders of calcium Ca₁₀(PO₄)₆F₂ and strontium-containing Ca₉Sr(PO₄)₆F₂ fluorapatites by both solid phase reaction method with subsequent heat treatment and chemical co-precipitation method from solutions of the initial components was investigated. It was shown that the total synthesis of calcium Ca₁₀(PO₄)₆F₂ and strontium-containing Ca₉Sr(PO₄)₆F₂ fluorapatites by solid phase method occurs at a temperature of 900 °C, and by chemical co-precipitation as a result of the reaction between initial components. Obtained nanosized powders of calcium and strontium-containing fluorapatites were produced by chemical co-precipitation method.